Production of a microemulsion of American genipa l. (rubiacea) bark extract and the antioxidant and antiparasitic activities (Research, Society and Development, 2022)
Genipa americana L. is a plant native to the Americas, popularly known in Brazil as Jenipapeiro, and is chemically characterized by the presence of genipin, which has pharmacological actions such as anti-inflammatory and antioxidant. The bark is used for its antiulcerogenic and antidiarrheal activities. Research developed for chemical knowledge have shown the plant is of interest for the production of efficient drugs such as antioxidants and antimicrobials. Free-living parasites, including those of the genus Acanthamoeba, have aroused interest and the study of plants used in folk medicine is a strategy for the discovery of conventional treatments to the infections caused by this parasite to be used pure or in preparations such as microemulsions (ME), which offer advantages related to the release of drugs and the absorption of the active ingredient. The aim of the study was to evaluate antiparasitic and antioxidant activities as well as to obtain a ME from the hydroethanolic extract (HEE) of G. americana. The DPPH free radical reduction method was used to evaluate the antioxidant activity of HEE, which showed an inhibition percentage (PI) of 47.82%. The antiparasitic activity of the HEE using A. castellanii trophozoites showed a PI of 80% at the highest concentration tested (9 mg mL-1). The ME containing 10% HEE was characterized for its droplet size (18.33 µm), pH (5.68) and polydispersity index (0.19). Therefore, the HEE presented antioxidant and antiparasitic effects, while its microemulsion showed potential to disperse particles.